2023
DOI: 10.1021/acs.nanolett.3c01738
|View full text |Cite
|
Sign up to set email alerts
|

1.89 $ kg–1 Lake-Water-Based Semisolid Electrolytes for Highly Efficient Energy Storage

Abstract: Solid electrolytes with fast ion kinetics and superior mechanical properties are critical to electrochemical energy devices; however, how to design low-cost, high-performance solid electrolytes has become a critical challenge in the energy field, and significant progress has not been achieved until now.Here, lake-water-based semisolid electrolytes with a low cost of 1.89 $ kg −1 have been put forward for the purpose of market promotion. By virtue of the palygorskite dopants and lake water source, the electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Originally used polyelectrolytes, including hydrogels and ionogels based on water and ionic liquids, were usually unstable with complicated ionic environments and caused inhomogeneous diffusion of cations and anions in electrochemical processes resulting in unstable energy transduction properties. , The slow ion mobility and long response time deteriorate the high-frequency response speed of IPMC devices. To this end, a single-ion conductive polyelectrolyte has been reported with one kind of movable ion in a polymer matrix (Figure a) .…”
Section: Materials Engineering For Addressing Critical Challengesmentioning
confidence: 99%
“…Originally used polyelectrolytes, including hydrogels and ionogels based on water and ionic liquids, were usually unstable with complicated ionic environments and caused inhomogeneous diffusion of cations and anions in electrochemical processes resulting in unstable energy transduction properties. , The slow ion mobility and long response time deteriorate the high-frequency response speed of IPMC devices. To this end, a single-ion conductive polyelectrolyte has been reported with one kind of movable ion in a polymer matrix (Figure a) .…”
Section: Materials Engineering For Addressing Critical Challengesmentioning
confidence: 99%
“…Highly efficient electrochemical energy storage devices including batteries and supercapacitors are emerging as critical energy supply for modern smart electronics. Flexible supercapacitors are a kind of electrochemical energy device by virtue of high power density, lightweight, flexibility, and long cycle life. However, the rate capability and stability of flexible supercapacitors are restricted by limited ion transfer kinetics caused by conventional transmembrane transport across thick solid electrolytes. , For instance, a hydrogel electrolyte based supercapacitor was found with serious capacity degradation of 75% as the charge–discharge rate increased from 1 to 10 A g –1 . It has seldom been reported that flexible supercapacitors work stably at high current rates beyond 20 A g –1 . , When compared with electrode and electrolyte materials, fast and stable interfacial ion transfer does matter under high-current-rate conditions, but exciting achievement on this direction has not been reported until now.…”
mentioning
confidence: 99%